2012
DOI: 10.1177/0884533612446706
|View full text |Cite|
|
Sign up to set email alerts
|

A.S.P.E.N. Position Paper

Abstract: The parenteral multivitamin preparations that are commercially available in the United States (U.S.) meet the requirements for most patients who receive parenteral nutrition (PN). However, a separate parenteral vitamin D preparation (cholecalciferol or ergocalciferol) should be made available for treatment of patients with vitamin D deficiency unresponsive to oral vitamin D supplementation. Carnitine is commercially available and should be routinely added to neonatal PN formulations. Choline should also be rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(114 citation statements)
references
References 222 publications
3
105
0
6
Order By: Relevance
“…Acute copper toxicity results in vomiting, diarrhea, acute kidney injury, hepatic necrosis, and death [3]. Wilson’s disease, a genetic abnormality of cellular transport, is an example of chronic copper toxicity.…”
Section: Trace Elementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Acute copper toxicity results in vomiting, diarrhea, acute kidney injury, hepatic necrosis, and death [3]. Wilson’s disease, a genetic abnormality of cellular transport, is an example of chronic copper toxicity.…”
Section: Trace Elementsmentioning
confidence: 99%
“…Wilson’s disease, a genetic abnormality of cellular transport, is an example of chronic copper toxicity. Symptoms of chronic toxicity include neurological disorders, renal insufficiency, and cirrhosis [3]. Blaszyk et al performed biopsies on 28 patients on long-term PN with intestinal failure-associated liver disease as well as 10 controls with drug-induced cholestatic liver disease and showed that 89% of PN patients versus all controls had mildly elevated hepatic tissue copper, but 29% of the PN patients had levels above 250 mcg/g, the diagnostic threshold for Wilson’s disease [15].…”
Section: Trace Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…La mayoría de estas recomendaciones fueron apoyadas por la European Society for Clinical Nutrition and Metabolism (ESPEN) (30) Ambos tienen como vehículo Intralipid 10% y tiene que aña-dirse a los lípidos o las emulsiones de NP con lípidos por lo que los niños que no requieran lípidos no pueden recibir vitaminas liposolubles con este preparado.…”
Section: Existen Multivitamínicos Intravenosos (Iv) Diseñados Para Peunclassified